2005
DOI: 10.1002/cphc.200400470
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Electrochemical Characteristics of La0.7Mg0.3Ni5.0−x(Al0.5Mo0.5)x Hydrogen‐Storage Alloys

Abstract: The structure, hydrogen-storage property and electrochemical characteristics of La(0.7)Mg(0.3)Ni(5.0-x)(Al(0.5)Mo(0.5))x (x = 0-0.8) hydrogen-storage alloys have been studied systematically. X-ray diffraction Rietveld analysis shows that all the alloys consist of an La (La,Mg)2Ni9 phase and an LaNi5 phase. The pressure-composition isotherms indicate that the hydrogen-storage capacity first increases and then decreases with increasing x, and the equilibrium pressure decreases with increasing x. Electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…The capacity at 233 K increases from 36 mAh g −1 (x = 0.08) to 256 mAh g −1 (x = 0.20), and then decreases to 127 mAh g −1 (x = 0.28). It is reported that the low temperature dischargeability is mainly affected by hydrogen diffusion rate in the bulk [18]. The analysis above shows that D is much larger when x is 0.20, so discharge capacity of alloy for x = 0.20 is larger than that of the other alloy electrodes.…”
Section: Resultsmentioning
confidence: 89%
“…The capacity at 233 K increases from 36 mAh g −1 (x = 0.08) to 256 mAh g −1 (x = 0.20), and then decreases to 127 mAh g −1 (x = 0.28). It is reported that the low temperature dischargeability is mainly affected by hydrogen diffusion rate in the bulk [18]. The analysis above shows that D is much larger when x is 0.20, so discharge capacity of alloy for x = 0.20 is larger than that of the other alloy electrodes.…”
Section: Resultsmentioning
confidence: 89%
“…In this work, the hydrogen diffusion process and the electrochemical kinetics of the tested oxide were investigated respectively by chronoamperometry and Tafel extrapolation techniques under different temperatures. The hydrogen diffusion coefficient ( D H ) was used to evaluate the mass transport properties of an alloy electrode . The hydrogen diffusion rate can be estimated by the slope of the linear portion of log( i ) versus time t curve (Figure ) by using the following expression: logi=log()±6FDHitalicda2()C0Csπ22.303DnormalHa2t …”
Section: Resultsmentioning
confidence: 99%
“…As an important kinetics property of the hydride electrode in battery, it is very significant to minimize the decrease of discharge capacity even at the high discharge current density [16]. Fig.…”
Section: High-rate Dischargeabilitymentioning
confidence: 99%